2014
DOI: 10.1111/bph.12851
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic tolerance to morphine is regulated by PPARγ

Abstract: BACKGROUND AND PURPOSEOpioid drugs are potent analgesics. However, their chronic use leads to the rapid development of tolerance to their analgesic effects and subsequent increase of significant side effects, including drug dependence and addiction. Here, we investigated the role of PPARγ in the development of analgesic tolerance to morphine in mice. EXPERIMENTAL APPROACHWe monitored analgesia on alternate days using the tail immersion test. , bid) accelerated the development of tolerance to its antinociceptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 60 publications
(66 reference statements)
1
22
0
Order By: Relevance
“…The role of PPAR signalling in the development or modulation of other chronic pain conditions, such as osteoarthritis, cancer pain and migraine requires further study, as does the interaction of PPAR signalling with other well‐characterized endogenous pain control systems and currently prescribed analgesics. On this latter point, the PPARγ agonist pioglitazone has been shown to attenuate tolerance to morphine in a rat model of inflammatory pain (Ghavimi et al ., , Ghavimi et al ., ) and in the mouse tail immersion test (de Guglielmo et al ., ). Similar potential synergistic antinociceptive interactions with the cannabinoid (Russo et al ., ) and TRPV1 (Ambrosino et al ., ) signalling systems have been reported.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The role of PPAR signalling in the development or modulation of other chronic pain conditions, such as osteoarthritis, cancer pain and migraine requires further study, as does the interaction of PPAR signalling with other well‐characterized endogenous pain control systems and currently prescribed analgesics. On this latter point, the PPARγ agonist pioglitazone has been shown to attenuate tolerance to morphine in a rat model of inflammatory pain (Ghavimi et al ., , Ghavimi et al ., ) and in the mouse tail immersion test (de Guglielmo et al ., ). Similar potential synergistic antinociceptive interactions with the cannabinoid (Russo et al ., ) and TRPV1 (Ambrosino et al ., ) signalling systems have been reported.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Therefore, exposure to MF 30 min after injection of morphine could not maintain the analgesic effect of morphine. Thermal hyperalgesia could be caused, in part, through postreceptor processes followed by repeated morphine injection, including opioid receptor downregulation, internalization [Guglielmo et al, ], downregulation of spinal glutamate transporters [Mao et al, ], reduction of µ‐opioid receptor signaling [Johnson et al, ], and the increase of nitric oxide [Jeong et al, ]. However, exposure to MF was unable to restore these changes in Exp.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid drugs are highly effective analgesics for the treatment of pain. However, chronic use for 7–9 days leads to the development of tolerance, drug dependence, and addiction [Guglielmo et al, ; Shokraviyan et al, ]. Opioid tolerance is a complex phenomenon, and multiple mechanisms are responsible for the development of tolerance to the analgesic effect of morphine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPARγ agonists have been shown to inhibit the expression of cytokines by monocytes/macrophages and microglia (36). Preclinical research further showed that PPARγ activation by pioglitazone (PIO) attenuated development of opioid tolerance (38) reduced heroin self-administration under a fixed-ratio and progressive-ratio schedule of reinforcement and heroin-induced increases in extracellular dopamine in the nucleus accumbens (39). …”
Section: Introductionmentioning
confidence: 99%